New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode - Potapov, Mikhail; Nakamori, Taizo; Saitoh, Seikoh; Kuznetsova, Natalia; Babenko, Anatoly (Zootaxa, 2017)
The paper concerns two species of Collembola having a strong spine armature at the end of abdomen. Sahacanthella saoriae sp.nov. (Hokkaido, Japan), the second species of the genus, is described. Octodonthophora ornata (Magadan district, Russia) is redescribed with remarks on its taxonomical position. A key to the world genera of Anurophorinae with anal spines is given. The genera having four anal spines on the fifth abdominal segment are illustrated. DNA sequences of genes for mitochondrial cytochrome c oxidase subunit I, 16S ribosomal RNA, and nucler 28S ribosomal RNA were sequenced as DNA barcodes for S. saoriae sp.nov. and several taxa of Anurophorinae.